Assessment of the Contamination of Some Food Crops Due to Mineral Deposits in Ondo State, Nigeria. - Nwankpa, Alexander (European Journal of Sustainable Development, 2024)
The most valuable minerals are found in large quantities in southwest Nigeria, particularly in Ondo State. As a result of the mineral presence, several areas of Ondo State are currently connected to significant levels of naturally occurring radioactivity. If properly managed and controlled, the mineral reserves are a boon to the Nigerian government, but the risks involved in their exploration and utilization also pose a serious threat to the state. It has an impact on the resources of land, air, and water used for agriculture and human habitation. As a result, the government wants to guarantee that food security is negatively impacted. That is, the Federal government of Nigeria works to ensure that everyone has access to enough safe, nutrient-dense food. This work allowed for the prediction of likely radiological health implications by analyzing baseline radiation levels in some of the most significant food crops in Ondo State. Because they meet the majority of food's nutritional needs, maize (Zea mays), yam (Dioscorea alata), and cassava (Manihot esculenta) tubers were gathered from the State's farmlands. The main crops grown and consumed in the communities are maize, yam, and cassava, thus these were the ones picked. Above all, there would have been additional food products including meat, vegetables, fish, and water if there hadn't been budgetary limitations. To ensure thorough coverage of the study area, Ondo State was split up into zones. The samples of maize (Zea mays), yam (Dioscorea alata), and cassava (Manihot esculenta) were dried at room temperature until they achieved a constant weight. For 28 days, they were maintained in a 1-liter Marinelli beaker after being ground, blended, and packaged in 250 g. This allowed them to reach secular equilibrium. Gamma-ray spectroscopy was utilized to ascertain the activity concentrations of Thorium-232, Potassium-40, and Radium-226 in the food samples. When measuring radioactivity concentration, the Hyper Pure Germanium (HPGe) detector is superior to other detectors in several ways, including high energy resolution, sensitivity, peak shape, stability, minimal background noise, and high accuracy. Nevertheless, HPGe detectors are more costly, necessitate liquid nitrogen, and are more vulnerable to radiation harm. To calibrate the Hyper Pure Germanium detector, standard radioactive sources were first used. Every sample was subjected to a 10-hour gamma counting process at Obafemi Awolowo University in Ile-Ife. In yam, the mean activity concentrations of Ra-226, Th-232, and K-40 were 1.91